Notes on the Nests and Prey of Six Species of Pison in Australia (Hymenoptera: Sphecidae) - Howard E. Evans; Robert W. Matthews; Allan Hook (Psyche: A Journal of Entomology)
In the course of studies on the behavior of ground-nesting Sphecidae in Australia, we have occasionally made observations on species that make free mud nests or that accept wooden trap nests (see Krombein, 1967, for technique). Chief among these are species of the genus Pison, which is abundantly represented in Australia. We report here on six species, four of which have not previously been studied (rufipes Shuckard, westwoodi Shuckard, marginatum Smith, and a species near tibiale Smith). Data on two additional species (ignavum Turner and spinolae Shuckard) confirm and enlarge upon previously published reports. Our specimens have been compared with identified material in the British Museum (Natural History), including the types of Smith's and Turner's species. Voucher specimens have been deposited in the Australian National Insect Collections, Canberra, and at the University of Queensland, Brisbane. Some of these observations were made by Evans and Matthews during the summer of I969–70, others by Evans and Hook during the summer of 1979–80.